Discussion of the complications generated by Stanisław Ignacy Witkiewicz’s concept of biological monadism - Kmiecikowski, Waldemar (Filozofia Chrześcijańska, 2022)
The article focuses on Stanisław Ignacy Witkiewicz’s metaphysical concept, namely biological monadism. According to Witkacy, the Whole of Existence constitutes a multiplicity of monads – Particular Existences. It is them – occurring in various configurations – that constitute the substantive foundation of reality. The essential characteristic of these monads is their corporeal character, which means that Witkiewicz’s Particular Existence constitutes an original unity of the temporal (duration) and spatial (expanse) component; a unity finding expression in the statement that the monad is a corporeal consciousness and in the Whole of Existence there is no place for the objective existence of inanimate matter. The article exposes an important limitation of Witkiewicz’s metaphysics. It seems that the permanent presence of the Infinite in Witkacy’s General Ontology results in the indelible Mystery of Existence, which neutralizes the ultimate status of the why question. Being in Witkiewicz’s perspective becomes mysterious, enigmatic and senseless but, at the same time, it is deprived of any trace of randomness. In this way the structure of Being included in Witkiewicz’s monadic categorial network excludes the sense of the why question related to the Whole of Existence.